2018
DOI: 10.1021/acsomega.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Deposition of Dye–Molecule Nanoparticles in the Nanogap of a Plasmonic Antenna

Abstract: Plasmonic nanostructures, which allow light focusing at the deep subwavelength scale, and colloidal nanoparticles with unique optoelectronic properties are nowadays fabricated with nanometer precision. However, to fully control and exploit nanoscale light–matter interactions in hybrid plasmonic–nanophotonic devices, both materials must be assembled in heterostructures with similar precision. Near-field optical forces have recently attracted much attention, as they can precisely trap and position nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Therefore, the "grip" exerted on nanomaterials by plasmonic optical tweezers or plasmonic optical trapping (POT) should be very strong [16][17][18] . Following early demonstrations, POT has undergone rapid growth, and has been used to trap various nanomaterials such as polymer beads 10,[19][20][21][22][23][24][25][26][27] , metallic nanoparticles 12,18 , quantum dots 13,28,29 , dye aggregates 30,31 , and so on. In addition to these hard nanospheres, we have demonstrated that POT is also applicable to soft materials such as flexible polymer chains homogeneously dissolved in water 32,33 .…”
mentioning
confidence: 99%
“…Therefore, the "grip" exerted on nanomaterials by plasmonic optical tweezers or plasmonic optical trapping (POT) should be very strong [16][17][18] . Following early demonstrations, POT has undergone rapid growth, and has been used to trap various nanomaterials such as polymer beads 10,[19][20][21][22][23][24][25][26][27] , metallic nanoparticles 12,18 , quantum dots 13,28,29 , dye aggregates 30,31 , and so on. In addition to these hard nanospheres, we have demonstrated that POT is also applicable to soft materials such as flexible polymer chains homogeneously dissolved in water 32,33 .…”
mentioning
confidence: 99%
“…On the contrary, dielectric particles such as polystyrene or biomaterials have small polarizability and are still difficult to be stably trapped. Given such a situation, some non-standard optical trapping techniques, such as plasmonic optical tweezers (Shoji and Tsuboi 2014;Ndukaife et al 2018;Pin et al 2018) or thermophoretic manipulation induced by photothermal effects (Duhr and Braun 2006;Jiang et al 2009;Maeda et al 2012;Lin et al 2018;, have been proposed. These non-standard optical trapping techniques can be combined with the present flow control concept in nanofluidic device to achieve more stable performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thermo-osmotic flows result from the surface tension gradient induced by a temperature gradient at the interface between a liquid and a substrate. Owing to the high temperature in a nanoscale region, a thermo-osmotic flow might be generated, which draws surrounding particles towards the heat source [79][80][81] .…”
Section: Plasmonic-thermal Effectsmentioning
confidence: 99%